A novel sufficient protection criterion based on adjacent maximal current differences. (December 2020) - Zheng, Jiaqi; Cao, Chengjie; Ren, Jiayi; Sun, Jinghui; Tian, Fangyuan
Abstract: It is hard for traditional current protection to solve problems of distribution networks with highly penetrative DGs. The fault information required by the most protection methods cannot be provided by the poor infrastructure of distribution networks. In this paper, a sufficient criterion based on the maximal current differences between adjacent transmission lines is proposed to promote selective configuration of protection scheme. The principle of the criterion and its advantages on current protection application are analyzed. The suppress influence of DG on the current of downstream transmission line current can be processed without high demand for communication in distribution network with DGs. Through the simulation in Matlab/Simulink, the effectiveness of the proposed criterion is validated.